2022
DOI: 10.1111/jonm.13537
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative study on barriers and facilitators of quality improvement engagement by frontline nurses and leaders

Abstract: Aim: This study aimed to understand the facilitators and barriers of quality improvement (QI) from the perspective of nurses and leaders at the frontline.Background: Nurse engagement in QI has been associated with quality care and improved patient outcomes, yet nurse reported participation is low.Methods: A descriptive qualitative design and purposive sampling was used to examine barriers and facilitators of nurse engagement.Results: Facilitators (1) A leader's influence on a QI culture. Subthemes: creating bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 25 publications
(42 reference statements)
2
8
0
Order By: Relevance
“…These data align with a qualitative study by Alexander and colleagues that found both culture and leadership were powerful "influencers" of frontline engagement in QI. 21 Nurses in the study expressed having a limited voice in practice decisions and feared being viewed as a troublemaker if they spoke up about QI issues. 21,22 Developing a just culture where nurses feel safe to report errors and all staff members are held to the same standards is critical for achieving positive patient outcomes.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…These data align with a qualitative study by Alexander and colleagues that found both culture and leadership were powerful "influencers" of frontline engagement in QI. 21 Nurses in the study expressed having a limited voice in practice decisions and feared being viewed as a troublemaker if they spoke up about QI issues. 21,22 Developing a just culture where nurses feel safe to report errors and all staff members are held to the same standards is critical for achieving positive patient outcomes.…”
Section: Discussionmentioning
confidence: 96%
“…21 Nurses in the study expressed having a limited voice in practice decisions and feared being viewed as a troublemaker if they spoke up about QI issues. 21,22 Developing a just culture where nurses feel safe to report errors and all staff members are held to the same standards is critical for achieving positive patient outcomes. Research is needed to study the relationship between a just culture and its impact on patient outcomes at the front line.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…However, issues regarding the selection of appropriate indicators to use, report and embed in clinical practice hinder their introduction in continuous quality assessment and improvement initiatives (Burston et al, 2013 ). A recent study indicated that barriers to quality improvement for nurse managers included a lack of timely data presented in a usable and easy‐to‐access manner (Alexander et al, 2022 ). Additionally, information needs vary between different actors and settings in health care, such as professionals, units and work shifts, creating a need for tailored and dynamic information systems, which respond to different users' individual needs (Peltonen et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%